PERAN GURU KELAS DALAM LAYANAN BIMBINGAN KONSELING SISWA KELAS IV SD NEGERI 1 HADIWARNO - Septiani, Ronaa Abiyyah; Purnamasari, Mega Isvandiana Purnamasari; Burhanuddin, Afid Burhanuddin (Scholarly Journal of Elementary School, 2025)
Abstract This research aims to describe: 1) the role of class teachers as implementers of guidance and counseling services in increasing the learning motivation of class IV students at SD Negeri 1 Hadiwarno; 2) implementation of counseling guidance services to increase learning motivation for class IV students at SD Negeri 1 Hadiwarno; 3) supporting and inhibiting factors for the implementation of counseling guidance services in increasing the learning motivation of class IV students at SD Negeri 1 Hadiwarno. This type of research is qualitative descriptive research. Data collection techniques in this research are observation, interviews, and documentation. The research results show: 1) the role of class teachers as implementers of counseling guidance services in increasing student learning motivation includes informers, motivators, mentors, facilitators, mediators and evaluators; 2) guidance and counseling services that have been implemented at SD Negeri 1 Hadiwarno, namely study guidance; 3) The supporting factor for the implementation of counseling guidance services is good cooperation between class teachers and other subject teachers, the inhibiting factor is the lack of knowledge regarding structured counseling guidance services Keywords: Guidance Counseling, Motivation, Teacher